(−1)n | ||
an= | ||
2n−1 |
−1 | (−1)n | 1 | ||||
oraz | ≤ | ≤ | ||||
2n−1 | 2n−1 | 2n−1 |
−1 | ||
Obliczam granicę limn→+∞ | ||
2n−1 |
−1 |
| 0 | |||||||||||||
limn→+∞ | = limn→+∞ | = | =0 | ||||||||||||
2n−1 |
| 2−0 |
1 | ||
Obliczam granicę limn→+∞ | ||
2n−1 |
1 |
| 0 | |||||||||||||
limn→+∞ | = limn→+∞ | = | =0 | ||||||||||||
2n−1 |
| 2−0 |
−1 | 1 | |||
Ponieważ limn→+∞ | = 0 oraz limn→+∞ | = 0 | ||
2n−1 | 2n−1 |
−1 | (−1)n | 1 | ||||
a także: | ≤ | ≤ | ||||
2n−1 | 2n−1 | 2n−1 |
(−1)n | ||
limn→+∞ | = 0 | |
2n−1 |